Three new species of Azana Walker (Diptera: Mycetophilidae: Sciophilinae) from South Korea - Lee, Dongho; Bae, Yeon Jae (Zootaxa, 2026)
The genus Azana Walker is a small group within the family Mycetophilidae, comprising 17 described species globally. However, it has not been previously studied in Korea. This study describes three new species of the genus from South Korea: Azana dentata sp. nov., Azana lunulata sp. nov., and Azana tricona sp. nov. The material examined, detailed descriptions, photographs of diagnostic characters, taxonomic remarks, and habitat and ecological notes are provided.